2012
DOI: 10.7196/samj.6009
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression and its risk factors: An urban prevalence study in KwaZulu-Natal

Abstract: Objective. There has been a recent increase in interest in antenatal depression, which is associated with adverse obstetric, neonatal and maternal outcomes and has been overlooked and underdiagnosed. Local data on prevalence and risk factors are lacking. Aim. To determine the prevalence and risk factors associated with antenatal depressive symptoms in a KwaZulu-Natal population. Methods. The Edinburgh Postnatal Depression Scale and a socio-demographic questionnaire in English and isiZulu were administered to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
142
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(170 citation statements)
references
References 21 publications
16
142
11
1
Order By: Relevance
“…2 Presence of depression during pregnancy in South Africa has indexes that vary and are superior to those seen in the present study, higher than 39%. 10 This may partly be the result of the nature of the selected sample and the methodology used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Presence of depression during pregnancy in South Africa has indexes that vary and are superior to those seen in the present study, higher than 39%. 10 This may partly be the result of the nature of the selected sample and the methodology used.…”
Section: Discussionmentioning
confidence: 99%
“…12 In accordance to other studies, 2,6 the present research shows that pregnant women who have history of mental disorder are more likely to experience depression during pregnancy. A study conducted in South Africa 10 showed that the previous history of depression was a significant risk factor for the development of depression during pregnancy. In this study, 35.7% of pregnant women who had at least one mental disorder prior to pregnancy had depression during pregnancy, suggesting that pregnant women who have experienced a mental disorder before pregnancy are at high risk of relapse in prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is suicide a leading cause of maternal death in the first year post-partum, but women tend to die violently by hanging or jumping as opposed to medication overdose, suggesting that the profile of women who complete suicide post-delivery is different to women in the general population [3]. Most research has been undertaken in the United States and Europe [4] finding prevalence ranging between 13% and 33% during pregnancy, and although there is a scarcity of research from low and middle income countries (LMICs), evidence of the pres-ence of suicide ideation during pregnancy in LMICs has emerged in the recent literature [4][5][6][7][8]. Research on antenatal depression in Bangladesh [6] found 14% suicide ideation among pregnant women who had screened positive for probable depression on the Edinburgh Postnatal Depression Scale (EPDS).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Pakistan [7], 11% of all pregnant women interviewed reported suicide ideation in the last two weeks of pregnancy, of whom 67/148 (45%) reported having attempted suicide. Recently, in an urban area of KwaZulu-Natal, South Africa [8], researchers screened women using the EPDS and found 38% had probable depression and high numbers of women reported suicide ideation in the previous seven days (145/380; 38.3%). In that study researchers found a significant association between probable depression and suicide ideation with risk factors including: being single and without support, being HIVpositive, having an unplanned pregnancy and a past history of depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation